2011
DOI: 10.1038/tpj.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

A genomic approach to predict synergistic combinations for breast cancer treatment

Abstract: We leverage genomic and biochemical data to identify synergistic drug regimens for breast cancer. In order to study the mechanism of the histone deacetylase (HDAC) inhibitors valproic acid (VPA) and suberoylanilide hydroxamic acid (SAHA) in breast cancer, we generated and validated genomic profiles of drug response using a series of breast cancer cell lines sensitive to each drug. These genomic profiles were then used to model drug response in human breast tumors and show significant correlation between VPA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…For the LINCS example (Figure 8(b)), positive objects mostly 571 have elevated expression for the two reported genes (GLRX and NME7) compared to 572 the negative objects. The direction of this differential gene expression for both genes is 573 consistent with literature for vorinostat experiments [32], [33]. These above two 574 examples illustrate how visualization of significant feature pairs can be a useful way to 575 explain the separability of object sets and understand the data.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…For the LINCS example (Figure 8(b)), positive objects mostly 571 have elevated expression for the two reported genes (GLRX and NME7) compared to 572 the negative objects. The direction of this differential gene expression for both genes is 573 consistent with literature for vorinostat experiments [32], [33]. These above two 574 examples illustrate how visualization of significant feature pairs can be a useful way to 575 explain the separability of object sets and understand the data.…”
supporting
confidence: 67%
“…One example is (GLRX, NME7) that is 531 especially good for separating vorinostat experiments from all others. Not only are both 532 of these genes known to have increased mRNA expression in response to 533 vorinostat [32], [33], but the two genes are annotated by STRING to both be in 534 database pathways of nucleotide biosynthesis, co-express with each other in other model 535 organisms, and mentioned together often in literature abstracts. Later, in Section 3.4, 536 we will demonstrate that the positive objects and negative objects are visually 537 separated under this feature pair, as in Figure 8.…”
mentioning
confidence: 99%
“…This builds on our previous work with gene expression-based signatures, which were derived using the same approach, and which showed that drug response signatures predict whether a tumor or cell line will be sensitive or resistant to a drug [49,51,52]. The rapamycin response signature contained 200 probe sets and represented 175 unique genes (See Table S4 in Additional file 5).…”
Section: Resultsmentioning
confidence: 99%
“…We previously published that inhibition of HDAC downregulates the MYC pathway in vitro. 3 In the tumor samples before and after VPA treatment in the VAST trial, we examined the gene expression patterns using gene set omic analysis (GSOA) and generally applicable gene set enrichment (GAGE). 34 , 35 By using either the C6 data sets ( P = .022 by GSOA; P = 4.47 × 10 −7 by GAGE) or the Hallmark pathway gene sets ( P = .001 by GSOA; P = 4.42 × 10 −61 by GAGE) from MSigDB, 36 genes regulated by MYC were downregulated in the post-treatment samples compared with the pretreatment samples.…”
Section: Resultsmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors have shown promise in breast cancer in vitro, although this promise has not yet translated to clinical benefit. HDAC inhibitors have multiple cellular effects, including increasing the expression of tumor suppression genes, 2 increasing the expression of cell cycle regulators, 3 increasing the expression of mediators of apoptosis, 4 - 7 decreasing proteasome-mediated degradation of tumor suppressor genes, 8 decreasing oncoprotein levels via loss of hsp90-mediated protection, 9 - 11 decreasing mitotic stability, 12 and decreasing angiogenesis. 13 , 14 HDAC inhibitors potentiate the apoptotic effect of anthracyclines on breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%